LAPORAN KASUS INFEKSI/INFLAMASI TRAKTUS GASTROINTESTINAL BAWAH ABSES PERIANAL DENGAN FISTULA - Gupita Nareswari; Tandy Chintya Tanaji; Mulia Rahmansyah; Partogi Napitupulu; Astien Astien; Revalita Wahab (Fakultas Kedokteran Universitas Trisakti, 2024)
Perianal abscess with perianal fistula is an infectious-inflammatory disease of the perianal region. This disorder has quite high morbidity and recurrence rates and is treated with surgery. Complete preoperative findings, including anatomy, the connection between the fistula and surrounding structures, and secondary fistulas and abscesses, can be obtained through radiological examination. In this case report, a painful lump that was actively producing pus was found in the perianal area, a perianal ultrasound (USG) and Magnetic Resonance Imaging (MRI) examination was carried out and the diagnosis made was a perianal abscess with fistula. Fistulectomy and abscess drainage were performed.